A new JCI conflict-of-interest policy. - Neill, US; Thompson, C; Feldmann, M; Kelley, W (2007)
As stewards of the JCI, we are responsible for instituting and sustaining the highest possible standards for integrity. To this end, we have established a very specific set of guidelines for handling potential conflicts of interest - not only for authors and referees, but also for ourselves.